Transformations in the governance of French medical laboratories - Antoine Leymarie (Revue de la Régulation)
In France, private medical laboratories (PMLs) were at the heart of the fight against the Covid-19 pandemic. Each year biological examinations account for over 70 % of all medical diagnoses. Although the health crisis put the spotlight on this sector, no targeted social science work has been carried out on it. However, since the early 2000s, PMLs have undergone significant changes in terms of concentration, industrialisation and financialisation that has radically changed the landscape of the sector. In the space of two decades, the number of PMLs has fallen from 4000 to around 300 and almost 80% of them are now owned by six financial groups. This article traces the history of this sector, from its “birth” in the 1970s to the present day, and through it, that of a profession: medical biologists. To do so, we mobilize the Régulation theory “sectoral approach” – which focuses on sectoral idiosyncrasies – enriched by the sociology of the professions. In the first section, we analyse the historical dynamics of the “French medical biology model” and its rise during the 1980s. Secondly, we examine the crisis of this model in the early 2000s, further to various reforms and because of the strategies of Private Equity and professional players. In section 3, we put forward an analysis of the new mode of regulation – industrial and financial – as well as the organisational and professional transformations that medical biologists are facing.